Sulcus Fixation of Foldable Intraocular Lenses Guided by Ultrasound Biomicroscopy - Shasha Gao; Tingyu Qin; Shengnan Wang; Yong Lu (Journal of Ophthalmology)
Background. To evaluate the clinical efficacy of suture fixation of foldable intraocular lens (IOL) in ciliary sulcus guided by ultrasound biomicroscopy (UBM). Methods. Thirty-five eyes of 32 cases needing suture fixation of foldable IOL in ciliary sulcus in our hospital were collected and divided into two groups: group A and group B. In group A, UBM was performed on 19 eyes of 17 cases before surgery to locate the projection position of ciliary sulcus in iris surface. In group B, the traditional sulcus fixation of IOL was performed on 16 eyes of 15 cases. The inserting position of needles, the haptics position of IOL and the IOL tilt, and decentration were observed by UBM examination 3 months after the surgery. Meanwhile, the vision and contrast sensitivity were analysed. Results. The differences in inserting position of the needle, the IOL tilt and decentration, the ratio of IOL haptics in sulcus, and uncorrected visual acuity were statistically significant (P<0.05). The differences in best corrected visual acuity (BCVA) and contrast sensitivity were not statistically significant (P>0.05). Conclusions. Sulcus fixation of foldable IOL aided by UBM can increase the accuracy of IOL haptics implanted into ciliary sulcus and reduce the IOL tilt and decentration.